ANALISIS POTENSI PENINGKATAN PENJUALAN TOKO MITRA LAZADA AZGALERY DENGAN ALGORITMA C4.5 - Fransisco, Rico Fransisco; Elisa, Erlin (Computer Based Information System Journal, 2024)
The potential for sales in online marketplaces is increasing over time due to the development and distribution of telecommunications signals and equipment. This event is an opportunity that can be exploited by partner shops selling on the marketplace, one of which is Azgalery Lazada partners. Azgalery has been around for 4 years with a total of almost 700 products in various categories ranging from women's fashion, men's fashion, home decoration to other household equipment. This research aims to help partner shops get a decision tree that can be used for making crucial decisions such as preparing the latest products and price research. Apart from that, this also increases the customer trust in the azgalery store itself so that they are more trustworthy in the eyes of customers. The method used is an implementation using data mining, especially classification using the C4.5 algorithm. This method is used to analyze sales potential with the help of existing data to support research to produce valid results.